1986
DOI: 10.1139/v86-021
|View full text |Cite
|
Sign up to set email alerts
|

Étude des Hernandiacées. XII. Dimères aporphine–benzylisoquinoléine originaux isolés de Hernandiapeltata

Abstract: Office de la recherche scientifique et technique d'outre-mer, B.P. 76,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…The chemical differences between the two specimens may be due to different edaphic conditions or different physiological stages at collection time, or may be genetically fixed. Such variations in alkaloid content have already been observed in Hemandia peltata (9,10) and in Albertisia papuana (11,12). This fact leads one to be cautious about the taxonomic significance of the occurrence of particular compounds.…”
Section: Resultsmentioning
confidence: 89%
“…The chemical differences between the two specimens may be due to different edaphic conditions or different physiological stages at collection time, or may be genetically fixed. Such variations in alkaloid content have already been observed in Hemandia peltata (9,10) and in Albertisia papuana (11,12). This fact leads one to be cautious about the taxonomic significance of the occurrence of particular compounds.…”
Section: Resultsmentioning
confidence: 89%
“…The contemporary literature revealed that the Malaysian species of H. peltata Meisn, used by the Samoan healers, has anti-hypertensive (Dittmar, 1991;Singh, 1986), antitumor (Pernet, 1971), piscicide (Nishino & Mitsui, 1973) and antiarteriosclerosis (Ebel & Roth, 1987) activity. H. peltata from Malaysia is reported to contain benzylisoquinoline alkaloid hebridamine (Chalandre et al, 1986) that inhibit chloroquine-resistant Plasmodium falciparum (Angerhofer et al, 1999), and artherosclerosis (Lakshmi et al, 2009). Moreover, the lignans such as podophyllotoxins (deoxypodophyllotoxin and deoxypicropodophyllin) isolated from H. peltata have anticancer activity (Pettit et al, 2004) while hernanol, benzopyran, epiaschantin and deoxypodorhizone inhibit Neisseria gonorrhoeae (Pettit et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Three 2 -or 6-noraporphine-benzylisoquinoline dimers 83-85 are listed in Table 8. Additionally, (+)-thalicarpine-2 -N-oxide (86), the only member of the thalicarpine type with a 2 -N-oxide functional group that was isolated from Hernandia peltate [110], is depicted in Figure 7. In addition, three 6a,7-dehydroaporphine-benzylisoquinoline dimers 87-89 are displayed in Table 9.…”
Section: Thalicarpine-type Dimersmentioning
confidence: 99%